Competing stakeholder discourses in constructing cultural heritage: The legal case of the house at No. 98 Hai’er Lane, China - Zhonghua Wu; Jian Li (Humanities & Social Sciences Communications)
Abstract In the process of urbanization, the balance and/or conflict between the conservation, development, and utilization of cultural heritage has become an emergent theme. This paper explores how such a theme is manifested through discourse by analyzing the legal case of the house at No. 98, Hai’er Lane, China, which is entangled with multiple narratives of the local community, various levels of courts, and government agencies regarding the value of this site. While the contested nature of discourses lies in the power asymmetry, there is some space to pose a challenge against the dominant discourse, e.g., adopting a multi-stakeholder approach to mediate various interests of stakeholders. Besides, disputes over heritage protection and promotion need to be understood within the dominant discourses of their time. Based on such understandings, cultural heritage, if taken as a social sign, particularly for its identification and conservation, may be subject to different constructions by sign users as society progresses. Considering that heritage protection law in China places a greater emphasis on taking cultural heritage as things than orientating cultural heritage to humans, it is desirable to address intricate tensions between the conservation, development, and utilization of cultural heritage by promulgating more systematic and explicit laws and regulations that better reflect the heteroglossia of stakeholders.